Unmasking Rosai-Dorfman disease in a woman with cervical lymphadenopathy: a histopathological insight - Doshi, Anoushka A.; Nelekar, Shruti B. (International Journal of Research in Medical Sciences, 2023)
Rosai-Dorfman disease (RDD) also called as sinus histiocytosis with massive lymphadenopathy is a rare benign proliferative self‐limiting disease of the macrophage‐histiocyte cell family. Its etiology is unknown and presents with massive lymphadenopathy. We hereby present a case of a female presenting with massive cervical lymphadenopathy, evening rise in temperature and weight loss. It was initially misdiagnosed as tuberculous cervical lymphadenopathy as it is the most common cause of cervical lymphadenopathy in India due to high prevalence of tuberculosis. It was treated with anti-tuberculous drugs, but did not resolve. Eventually neck biopsy was done which showed characteristic histopathologic features including emperipolesis and S100 positivity on immunohistochemistry. The patient was managed conservatively with observation and symptomatic management. Patient underwent spontaneous remission in a few months. The absence of any specific clinical features caused diagnostic difficulty, delaying the diagnosis. This report highlights the importance of considering RDD in the differential diagnosis of cervical lymphadenopathy, particularly in tuberculosis-endemic regions.